A guideline update for the practice of echocardiography in the cardiac screening of sports participants: a joint policy statement from the British Society of Echocardiography and Cardiac Risk in the Young. Issue 1 (March 2018) - Oxborough, David; Augustine, Daniel; Gati, Sabiha; George, Keith; Harkness, Allan; Mathew, Thomas; Papadakis, Michael; Ring, Liam; Robinson, Shaun; Sandoval, Julie; Sarwar, Rizwan; Sharma, Sanjay; et al.
Abstract : Sudden cardiac death (SCD) in an athlete is a rare but tragic event. In view of this, pre-participation cardiac screening is mandatory across many sporting disciplines to identify those athletes at risk. Echocardiography is a primary investigation utilized in the pre-participation setting and in 2013 the British Society of Echocardiography and Cardiac Risk in the Young produced a joint policy document providing guidance on the role of echocardiography in this setting. Recent developments in our understanding of the athlete's heart and the application of echocardiography have prompted this 2018 update.